Ocean observation system design of mooring buoy and benthic node with electro-optical-mechanical cable - Zhang, Shaowei; Tian, Chuan; Zhou, Fenghua (Frontiers in Marine Science, 2022)
For the seafloor and sea surface long-term, multi-parameter observatories in the ocean, we design the hybrid system, named Mooring Buoys Observation System for Benthic with Electro Optical Mechanical Cable (MBOSBC). The Electro Optical Mechanical (EOM) cable connects the sea surface buoy and seafloor junction box, so as to establish the transmission link of information and power between sea surface and seafloor. Also, EOM cable playing the role of mooring tether of MBOSBC has to withstand the rigorous marine environment, so as to experience mooring loads under complex marine environment conditions for long terms. The data transmission of the system includes EOM, satellite, wireless radio, and acoustic. The system power generated by the wind turbine and solar panel, is transmitted to the seafloor junction box. The acoustic communication instrument is utilized to gather the sample data from other benthic node, such as seafloor lander, AUV and underwater gliders. MBOSBC is designed to operate from shallow water to deep sea, and to simultaneously monitor the sea surface hydrology, meteorology and water quality, and the benthic temperature, pressure, salinity, currents, seafloor video. Moreover, the data is transmit in real-time mode, so the scientists can integrate the data assimilation result and MBOSBC observatories process to optimize the observation. We give the MBOSBC architecture design including mechanical design, control, power, data transmission, EOM cable and so on. And at last, we describe the launch and recovery process of MBOSBC, and experiment results.